Single and multiple dose evaluation of a novel MetAP2 inhibitor: Results of a randomized, double‐blind, placebo‐controlled clinical trial. Issue 8 (23rd April 2018) - Malloy, Jaret; Zhuang, Dongliang; Kim, Terri; Inskeep, Phil; Kim, Dennis; Taylor, Kristin
Abstract : Aims: Methionine aminopeptidase 2 (MetAP2) inhibition has been shown to result in significant weight loss and improved glucose control. This Phase 1 clinical trial assessed the safety and tolerability, pharmacokinetics and preliminary efficacy of a novel MetAP2 inhibitor, ZGN‐1061. Methods: This clinical trial included a single ascending dose (SAD) phase in healthy subjects (BMI, 23 to <30 kg/m 2 ) and a multiple ascending dose (MAD) phase in otherwise healthy subjects (BMI, 27 to 40 kg/m 2 ). SAD phase doses, administered subcutaneously (SC), were 0.2, 0.6, 1.2, 2.4, 3.6 and 4.8 mg and the MAD phase evaluated doses of 0.2, 0.6 and 1.8 mg twice weekly SC for 4 weeks. Results: The SAD phase included 39 subjects (ZGN‐1061, N = 28; placebo, N = 11); 90% were male and BMI was 26.4 kg/m 2 . ZGN‐1061 was well tolerated across all doses, with the most frequent adverse events being mild headache and procedural‐related irritation. There were no severe or serious adverse events. All doses of ZGN‐1061 were rapidly absorbed and cleared, resulting in short duration of exposure that is anticipated to minimize potential off‐drug target risks. The MAD phase included 29 subjects (ZGN‐1061, N = 22; placebo, N = 7); 76% were male and BMI was 33.5 kg/m 2 . Safety observations were consistent with SAD findings. Efficacy measures in the MAD phase indicated trends for weight change (−1.5 kg total ZGN‐1061 vs −0.2 kg placebo) and other biomarker changes. Conclusions: ZGN‐1061 was well tolerated with no safety signals in all doses tested. In addition, the desired pharmacokinetic profile and preliminary efficacy observations with ZGN‐1061 support evaluation in larger and longer clinical trials.